The characteristics of traumatic spinal cord injuries at a referral hospital in Northern Tanzania - Rashid, Sakina Mehboob (Spinal Cord Ser Cases, 2017)
STUDY DESIGN: Retrospective study. OBJECTIVES: To describe the epidemiology of traumatic spinal cord injury (TSCI) in Northern Tanzania. SETTING: Main referral hospital for Northern Tanzania. METHODS: A retrospective review of 125 TSCI cases admitted to Kilimanjaro Christian Medical Centre (KCMC) over a period of 5 years. RESULTS: We included 125 patients in the sample size, with a male majority of 107 (85.6%), giving a male-to-female ratio of 5.9:1. The mean age at injury was 39.9 (±16.0) years. Overall, 66 (52.8%) were farmers and an overwhelming majority (109 (87.2%)) were referrals from peripheral medical centres. Fall injuries accounted for 65 (52.0%) of the admissions and 49 (39.2%) were injured due to a Road Traffic Accident (RTA). Severity of injury was classified according to the American Spinal Injury Association Impairment Scale (AIS) and 57 (45.6%) injuries were categorised as AIS A and 68 (54.4%) as AIS BCD. Cervical level injuries (59 (47.2%)) were the most frequent among the cohort. The in-hospital mortality rate was 24.1%. CONCLUSION: The majority of patients affected by TSCIs were young males and the most common cause was fall injuries. Cervical level injuries were the most common and in-hospital mortality was high.